The Journey To Find Personal Identity Of Tris InDivergent Novel By Veronica Roth (2011): An Individual Psychological Approach - Maulida, Nur Adnin; , Dr.Phil. Dewi Candraningrum, M.Ed (2016)
The study is aimed to show the personal identity of Tris, the main character in Veronica Roth's Divergent. The object of the study of this research is to analyze the novel based on its structural elements and the personal identity that deals with fictional finalism, striving for superiority, inferiority feeling, style of life, social interest, and creative power using individual psychological approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is taken from the novel Divergent written by Veronica Roth in 2011. While the secondary data sources are other materials taken from literary books, criticism, essays, articles, journal and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis, it shows that the character and characterization, setting, plot, style and theme of the novel are related into solid unity. Secondly, based on individual psychological approach the novel tells that the major character, Tris has different personal identity. The focus of this research is the main character in this novel, who is Tris. The purpose of this study is to find out how Tris achieves a process of individuation that is buried within her unconscious mind where the collective unconscious lies. To achieve individuation, Tris must reveal the archetypes that are buried within her and accept it as part of her personality His great ambition to be show the world that her personal identity is not dangerous.